Strategi Pengembangan Bisnis PT. Adhi Persada Properti: Business Development Strategy of PT. Adhi Persada Properti - Muhammad Irdy Eka Mahendra; Mukhamad Najib; Kirbrandoko Kirbrandoko (School of Business, Bogor Agricultural University (SB-IPB), 2020)
The property industry is a highly developed industry in Indonesia. Several factors such as infrastructure development (toll roads, railroads, public transportation, etc.), the need for shelter, increasing population, etc. PT. Adhi Persada Properti (APP) is a subsidiary of PT. Adhi Karya (Adhi) which delayed the purchase of property in the industry (apartments, housing, etc.). The objectives of this study are internal, external, key success factors in the property industry and the Business Model Canvas to identify business models with the results of long-term and short-term strategies for APP to improve competitiveness in the property industry. Data analysis methods and methods used are PEST Analysis, Focus Group Discussions, and Business Model Canvas. The results show that APP's main threat as an apartment and housing developer is in terms of regulations. Opportunities that can be utilized by APP through external analysis are the level of public purchasing power, economic growth and advancement in information technology. The level of purchasing power and economic growth is more influential on the sale of APP products. The BMC results of identification of each section in APP can be clearly mapped, which parts should be developed and which are maintained as they are at present. Keywords: property, external and internal issue, business model canvas, strategic planning